Penerapan Model Pembelajaran Kreatif Produktif Untuk Meningkatkan Aktifitas Belajar Mahasiswa Melalui Lesson Study Di Program Studi Pendidikan Pancasila Dan Kewarganegaraan - Sawaludin Sawaludin; Zedi Muttaqin; Sina Sina; Saddam Saddam (Universitas Muria Kudus, 2019)
This activity includes lesson study activities developed with three cycles through three stages, namely plan, do and see. This activity aims to improve student learning activities through the application of productive creative learning models. This activity was carried out in the fifth semester Pancasila education and citizenship education program Muhammadyah Mataram University, three cycles or three meetings (3 x 90 minutes), on the topics of learning theories, learning media, and information technology. From the results of the activity data it can be concluded that, the stages of productive creative learning that have been applied have succeeded in increasing student learning activities. This is because, all stages of learning activities emphasize the involvement of students from the beginning to the end of learning. Besides that, lecturers position themselves as facilitators and facilitators that are good for student learning activities. The implementation of the lesson study during the activity also strengthened the legality between the LS team, formed mutual learning (mutual learning), and increased the professionalism of lecturers as educators and instructors.